# Solve for y w*(yz)*4=zy*w w⋅(yz)⋅4=zy⋅w
Move 4 to the left of wyz.
4wyz=zyw
Move all terms containing y to the left side of the equation.
Subtract zyw from both sides of the equation.
4wyz-zyw=0
Subtract zyw from 4wyz.
Move y.
4wyz-1wyz=0
Subtract wyz from 4wyz.
3wyz=0
3wyz=0
3wyz=0
Divide each term by 3wz and simplify.
Divide each term in 3wyz=0 by 3wz.
3wyz3wz=03wz
Simplify 3wyz3wz.
Cancel the common factor of 3.
Cancel the common factor.
3wyz3wz=03wz
Rewrite the expression.
wyzwz=03wz
wyzwz=03wz
Cancel the common factor of w.
Cancel the common factor.
wyzwz=03wz
Rewrite the expression.
yzz=03wz
yzz=03wz
Cancel the common factor of z.
Cancel the common factor.
yzz=03wz
Divide y by 1.
y=03wz
y=03wz
y=03wz
Simplify 03wz.
Cancel the common factor of 0 and 3.
Factor 3 out of 0.
y=3(0)3wz
Cancel the common factors.
Factor 3 out of 3wz.
y=3(0)3(wz)
Cancel the common factor.
y=3⋅03(wz)
Rewrite the expression.
y=0wz
y=0wz
y=0wz
Divide 0 by wz.
y=0
y=0
y=0
Solve for y w*(yz)*4=zy*w

## Our Professionals ### Robert Kristofer ### Anna Frok ### Magnus Flores ### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top